SOSIALISASI TEKNIK PEMBESARAN IKAN NILA (OREOCHROMIS NILOTICUS) MENGGUNAKAN KOLAM TERPAL WADAH BUDIDAYA DI DESA TIGARAS - Submission AJP; Edward Zega; Tresi Rumapea; Nur Jannah; Ria Retno (Abdi Jurnal Publikasi, 2025)
Tarpaulin ponds are the right fish farming container for tilapia enlargement because of its various advantages such as ease of moving, friendliness to soil construction, suitability to the characteristics of tilapia, ease of cleaning the pond and harvesting fish. This community service activity aims to provide education to business groups through cognitive aspects about tilapia enlargement cultivation in tarpaulin ponds in the community in Labuhan Hamlet, Tigaras Village. This community service includes field visits (surveys), counseling, training, evaluation, and monitoring after counseling and training. So far, the target community group in Labuhan Hamlet has been able to design, build their own ponds, and be able to cultivate tilapia using tarpaulin ponds. Furthermore, the results of evaluation and monitoring show that the people of Labuhan Hamlet do not face significant obstacles in cultivating fish in tarpaulin ponds. Some of them even tried to design and build their own tarpaulin ponds independently. This is a strong indication of the openness and acceptance of the Labuhan Hamlet community towards the application of fish farming technology that is still relatively new to the Labuhan Hamlet community.